Literature Review: Hubungan Penggunaan APD dengan Kejadian Penyakit Dermatitis pada Nelayan - Shelsi Yulia Astri; Nur Ainun Waruwu; Anissa Sabillah Hutasuhut; Chairul Imam; Reni Agustina Harahap (Universitas Batanghari Jambi, 2023)
Dermatitis is an infection that occurs on the skin which is characterized by red nodules and itching. Fishermen are one of the workers who are most likely to suffer from dermatitis. The purpose of this research is to analyze the relationship between the use of APD and the incidence of dermatitis experienced by fishermen due to work. The research method used is a literature review, which is a collection of several daily articles from 2018-2022 using the keywords